The role of satellite channels in forming public opinion during the Syrian crisis- Field study in the Faculty of literature, University of Damascus - (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The objective of the research is to identify the relation between exposure to television viewers and their formation of public opinion on a particular problem, namely, extremism among university students at Damascus University, based on gender variables, economic level and place of residence. The questionnaire was distributed to a sample of 206 students And a student and students of the Faculty literature at the University of Damascus, and then been analyzed, and interpretation of the results scientific explanation and comes the importance of this research because it means a phenomenon in the Syrian society, which suffers from unrest since 2011, There was a link between watching satellite channels and forming a public opinion on the subject of extremism